The Influence of Work Motivation and Job Satisfaction on the Quality of Service of UPT RSUD Haji, South Sulawesi Province - Muhammad A; Nurmadhani Fitri Suyuthi; Mujahid (Jurnal Sinar Manajemen, 2024)
This study aims to determine the influence of work motivation and job satisfaction together on the quality of service of UPT RSUD Haji, South Sulawesi Province. This research was conducted at UPT Haji Hospital, South Sulawesi Province. This research is quantitative research based on the philosophy of positivism. Data collection for this study used questionnaires and documentation. The sample used was 84 respondents taken from employees of Haji Hospital, South Sulawesi Province. Determination of the sample used the Slovin formula. The analysis technique used was multiple linear regression analysis and statistical tests using SPSS. Before conducting multiple linear regression analysis, research instrument testing and classical assumption tests were carried out for the accuracy of the regression analysis results. The data sources used in this study were primary data and secondary data. The results of the study indicate that work motivation and job satisfaction have a simultaneous effect on the quality of service at the UPT RSUD Haji, South Sulawesi Province, where the calculated F is greater than the F table, namely 167.051> 3.109. When employees are motivated and also satisfied with their work, they tend to show optimal performance and provide better service. The results of this study also provide a strong basis for developing policies in hospitals. Policies that support improving health service quality standards can help improve overall service quality.